Synopsis of the Rosaceae of La Pampa, Argentine (Semiárida, 2020)
In this work, 15 species belonging to 13 genera are recorded. Keys for genera and species identification are attached. The valid name, synonyms and popular name, of each taxon, are given; also the bibliography of the first citation, iconography, distribution and frequency In La Pampa and a selected examined herbarium specimen.
Keywords: Rosaceae; La Pampa